Marital rape - should it be codified in the penal code of Malaysia / Mohd Shaqib Shamsher, Ahmad Zulfadli Ibrahim and Mawar Ahmad Fadzil - Shamsher, Mohd Shaqib; Ibrahim, Ahmad Zulfadli; Ahmad Fadzil, Mawar (2008)
This research had one primary objective: to stimulate everyone's conscience in understanding and acknowledging that marital rape is not a myth; but a reality that really occurs in our society. Marital rape has always been seen as propaganda of western human rights movement to indoctrinate our society. However, this research clearly highlights that there are boundaries and limitations that a husband cannot breach to his wife. The sanctity of a marriage must be preserved and not become an excuse for husbands' exploitation over the wife especially in their sexual lifestyles. Force and injury upon the wives for fulfilling lust isn't a moral reflection of our customs and religious values'. Hence, this research seeks to identify the genesis of marital rape and how it could be codified into our local laws for increasing effective enforcement in handling such issues. This is done by looking into three perspectives of marital rape. The local perspective in the Penal Code, the Islamic perspective and the Common Laws' approach to this issue. Based on our arguments, there are specific recommendations made for two main groups i.e. the Muslims and the non-Muslims. The basis of our recommendations for both groups is to perceive the spouses as one entity instead of two entities as prescribed by the Common Law. This is because of the relatively differed grounds of a marriage institution that exists in Malaysia in comparison to The UK. If this basis takes precedence, it would facilitate both the Civil and the Syariah Courts to recognize the offence and protect the victimized wives. Thus, the victimized wife of marital rape or sexual abuse or force could be reduced. In conclusion, it is hopeful for this research to relate to as many victimized women as possible to take necessary action to protect their rights against their ab4sive husbands. Namely, resorting to legal advice at NGO's and not hesitating to report to enforcement agencies. Besides that, this research would also hope for members of the legislature to prioritize marital rape in the parliament so an expedient action could be taken to remedy the flaws in our laws to deal with marital rape issues more effectively.